2009
DOI: 10.1097/sap.0b013e3181788ec9
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering in Plastic Surgery

Abstract: Tissue engineering is an interdisciplinary field that applies the principles of engineering and life sciences toward the development of biological substitutes that restore, maintain, or improve tissue function. This field has enjoyed tremendous growth in the past 10 years fuelled by its potential role in regenerating new tissues and naturally healing injured or diseased organs. Stem cells due to their pluripotentiality and unlimited capacity for self-renewal, may allow significant advances for distinct reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…72-76 Because primary cells from vocal fold tissue are not readily available and would not be a clinically viable selection, human bone-marrow derived MSCs were employed in cell studies; these cells are appropriate for future use in vocal fold cell-gel therapies. The ability of the cross-linked RGD-containing RLP-based hydrogels to support the attachment of hMSCs was investigated via seeding cells on the surface of 20wt% hydrogels with a 50% RLP and 50% RLP-RGD composition.…”
Section: Resultsmentioning
confidence: 99%
“…72-76 Because primary cells from vocal fold tissue are not readily available and would not be a clinically viable selection, human bone-marrow derived MSCs were employed in cell studies; these cells are appropriate for future use in vocal fold cell-gel therapies. The ability of the cross-linked RGD-containing RLP-based hydrogels to support the attachment of hMSCs was investigated via seeding cells on the surface of 20wt% hydrogels with a 50% RLP and 50% RLP-RGD composition.…”
Section: Resultsmentioning
confidence: 99%
“…The field combines cell transplantation, biomaterial science, bioengineering techniques and biochemical expertise to deliver both biologic and artificial components for permanent repair, designed specifically for the patient [1]. The ideal properties of a biomimetic scaffold include; good and rapid adherence; ease of handling and application; rapid bio-integration allowing neovascularisation; and, it must provide an environment that supports cell attachment, growth, proliferation and formation of extracellular construct (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…f 7) or still through integration: (14) By inverting it, the solutions class is obtained: (15) where sn is Jacobi's elliptic function of module k [34]. For 0  k , the relation (15) can be approximated by: (18) we can "control" and "direct" the potentiality of informational energy in the Onicescu sense (for details, see [35]).…”
Section: Theoretical Mathematical Modelmentioning
confidence: 99%
“…It has also been found that platelets density in the carrier system is overwhelming important in stimulating the bone repair process. Although most studies indicate a 5-to 10-fold higher platelet density at the PRP level than serum levels, the ratio in which platelet concentrate to the carrier system should be used is unknown [13,14].…”
mentioning
confidence: 99%